1977
DOI: 10.1128/iai.16.1.318-327.1977
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Invertases of Streptococcus mutans

Abstract: Sucrase activity was studied in 13 strains of Streptococcus mutans representing the five Bratthall serotypes. Sucrose-adapted cells have sucrase activity in the 37,000 x g-soluble fraction of all strains. The enzyme was identified as invertase (,B-D-fructofuranoside fructohydrolase; EC 3.2.1.26) because it hydrolyzed the 83-fructofuranoside trisaccharide raffinose, giving fructose and melibiose as its products, and because it hydrolyzed the f3-fructofuranoside dissacharide sucrose, giving equimolar glucose and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
9
0

Year Published

1979
1979
1987
1987

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 32 publications
4
9
0
Order By: Relevance
“…KusAMiTZu (11) found that the cariogenic Streptococcus mutans GS-5 possessed Pfructosidase activity, because partially purified enzymes (both extracellular and intracellular) hydrolyzed p-fructosides, but not a series of agiucosides. Similar observations were made by CHASSY et al (4) witb extracellular invertases from seven known oral streptococci (including five S. mutans strains), and by TANZER et al (21) with intracellular invertases isolated from the five Brathall serotypes of S. mutans. These studies mentioned that no splitting of maltose from tbe oral streptococci strains was obsei-ved by the enzyme extract.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…KusAMiTZu (11) found that the cariogenic Streptococcus mutans GS-5 possessed Pfructosidase activity, because partially purified enzymes (both extracellular and intracellular) hydrolyzed p-fructosides, but not a series of agiucosides. Similar observations were made by CHASSY et al (4) witb extracellular invertases from seven known oral streptococci (including five S. mutans strains), and by TANZER et al (21) with intracellular invertases isolated from the five Brathall serotypes of S. mutans. These studies mentioned that no splitting of maltose from tbe oral streptococci strains was obsei-ved by the enzyme extract.…”
Section: Discussionsupporting
confidence: 81%
“…Previous investigations (4,11,21) have claimed that the invertases in dental piaque are a-glucosidases or p-fructosidases, p-fructosidases being the m:ore important. It appears possible by the use of acarbose to obtain further information about this subject, Therefore, the aim ofthe present investigation was to examine the effect of acarbose (BAY g 5421) on the disaccharide splitting enzymes in the dentaf plaque and to determine the type of invertases present in the plaque.…”
mentioning
confidence: 95%
“…Homogenate concentration was 10 mg/ml acetate buffer. 28,30,31). The present investigation with plaque homogenate has shown the apparent pH optimum of pH 5.9 for the invertases to be lower than that for the glycosyltransferases.…”
Section: Discussionmentioning
confidence: 47%
“…The presence in the sample of saliva, blood and dental calculus can easily result in an erroneous quautitation of the invertase activity. Furthermore inorganic phosphate from the calculus may have a strong positive effect on the invertases (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation